Control and Monitoring System of IOT-Based Orchid Culvivation - Elsyea Adia Tunggadewi; Muhammad Hizbullah Imansyah (International Journal of Computer, Network Security and Information System, 2023)
Abstract—This study focuses on orchid plants, specifically the Phalaenopsis species, commonly known as the moth orchid, which is popular in Indonesia due to its beauty and stable flower prices. Orchid cultivation requires special attention to environmental factors such as light intensity, temperature, air humidity, and soil moisture. To enhance the efficiency of plant care, this research designs an Internet of Things (IoT)-based control and monitoring system. The system utilizes DHT22 sensors to monitor temperature and air humidity, BH1750 sensors to measure light intensity, and soil moisture sensors to measure soil moisture. The data collected by these sensors are transmitted in real-time to a NodeMCU ESP32 connected to the Firebase platform. Users can monitor and control plant conditions through an Android application linked to Firebase. Testing indicates that the sensors used provide accurate results in monitoring soil moisture. The water pump control system based on soil moisture and air humidity has proven effective, with consistent responses to environmental changes. This system is expected to assist cultivators in improving water usage efficiency and plant condition monitoring. The implementation of IoT technology in orchid cultivation can be an innovative solution to enhance the quality and quantity of ornamental plant production in the future.